Chapter 26: Challenges to feminist knowledge? The economisation of EU gender equality policy - Elomäki, Anna (Edward Elgar Publishing, 2023)
Although the European Union (EU) is often seen as a progressive gender equality actor, its neoliberalised economic policies are hostile to gender equality. The EU's gender equality policy has always been tied to the EU's economic priorities, and in the aftermath of the financial and economic crisis of 2007-2008 some EU institutions have explicitly promoted arguments about the benefits of gender equality for economic growth and competitiveness. This chapter maps the actors, processes and knowledge that have contributed to the neoliberal economisation of EU's gender equality policy and asks how the proliferation of arguments and knowledge about macroeconomic benefits has affected these policies. The chapter argues that economisation limits the possibilities of feminist governance actors and feminist knowledge to challenge the EU's gendered economic policies and the economic priorities, ideas and values that shape its gender equality policy.